Statement of the Section Internal Medicine of the DEGUM – Ultrasound Obtains Pole Position for Clinical Imaging in Acute Diverticulitis (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
This paper reviews and interprets the role of ultrasonography in view of the recently published Guideline on diverticular disease of the Consensus conference of the German Societies of Gastroenterology (DGVS) and Visceral Surgery (DGAV) implying a new classification of diverticular disease (CDD). Qualified US is not only equipotent to qualified CT and frequently effectual for diagnosis but considers relevant legislation for radiation exposure protection. Unsurpassed resolution allows detailed resolution thereby allowing to differentiate and stratify the relevant types of diverticular disease. Subsequently, US is considered the first choice of imaging in diverticular disease. Vice versa, CT has definite indications in unclear / discrepant situations – or insufficient US-performance.
Keywords: Diverticulitis; diverticular disease; intestinal ultrasonography; ultrasound